Glomerular injury is associated with severe courses of orthohantavirus infection - Nußhag, Christian; Uhrig, Josephine; Gruber, Gefion; Schreiber, Pamela; Zeier, Martin; Krautkrämer, Ellen (Pathogens, 2024)
Hemorrhagic fever with renal syndrome (HFRS) induced by Eurasian pathogenic orthohantaviruses is characterized by acute kidney injury (AKI) with often massive proteinuria. The mechanisms of the organ-specific manifestation are not completely understood. To analyze the role of glomerular and tubular damage in kidney injury induced by HFRS, we measured specific markers in urine samples of patients with acute Puumala virus (PUUV) infection and determined their correlation with disease severity. Levels of α1-microglobulin (α1-MG) and kidney injury molecule 1 (KIM-1), which is expressed by injured tubular epithelial cells, were measured to detect tubular dysfunction and injury. Immunoglobulin G (IgG) and the podocyte specific protein nephrin served as markers for glomerular injury. All four markers were elevated on admission. Markers of glomerular injury, IgG and nephrin, correlated with markers of disease severity such as length of hospitalization, serum creatinine, and proteinuria. In contrast, tubular injury did not correlate with these severity markers. Our results demonstrate that hantavirus infection induces both glomerular and tubular injury early in the clinical course. However, the glomerular dysfunction and podocyte injury seem to contribute directly to disease severity and to play a more central role in HFRS pathogenicity than direct damage to tubular epithelial cells.
Gesehen am 07.02.2025